PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN SUNGAI KAKAP - B31111011, MOPA RIZAL (Jurnal Manajemen Update, 2016)
One of competitive advantages of an organizational is a good job performance of the employees. Leadership styles and job satisfaction constitute factors considered are able to increase employees’ job performance. This study was a case study to analyze the influence of leadership styles and job performance towards employees’ job performance at Department of Industry and Trade in Pontianak, West Kalimantan province. The method employed in this study was survey and explanatory research, with 30 populations of employees were surveyed. Two hypotheses namely, relationship between leadership styles and job performance and relationship between job satisfaction and job performance used in this study.Result finding indicated that leadership styles and job satisfaction significantly influenced job performance of the employees. Keywords : Leadership styles, Job satisfaction, Job performance, Survey and Explanatory research